Highly nonlinear solitary waves for the detection of localized corrosion. (21st July 2020) - Jalali, Hoda; Rizzo, Piervincenzo
Abstract: This paper investigates the application of highly nonlinear solitary waves as a nondestructive evaluation method to detect localized corrosion in metallic structures. An experiment was conducted by using chains of monoperiodic particles in contact with a steel plate subjected to localized accelerated corrosion. A few damage-sensitive features were extracted from the time waveforms and fed into a multivariate statistical analysis to enhance the sensitivity of the proposed non-invasive monitoring approach. The experiment was complemented by a finite element model to quantify the effects of localized corrosion on certain features of the solitary waves propagating along the chain. Both the numerical and the experimental results show that the solitary waves reflected at the chain-plate interface are affected by the presence and progression of corrosion. Furthermore, the multivariate statistical analysis improved the sensitivity of the proposed approach. In the future, the proposed method may be implemented in those applications in which high temperature or radioactive environments are detrimental for the use of piezoelectric based ultrasonic testing.